2021
DOI: 10.6061/clinics/2021/e2226
|View full text |Cite
|
Sign up to set email alerts
|

High serum superoxide dismutase activity improves radiation-related quality of life in patients with esophageal squamous cell carcinoma

Abstract: OBJECTIVES: Esophageal squamous cell carcinoma (ESCC) is one of the most common malignant tumors in China. Intensity-modulated radiation therapy and volume-modulated arc therapy have become the main treatments for esophageal carcinoma; however, side effects caused by radiotherapy greatly impact the quality of life in these patients. This study aimed to explore the impact of serum superoxide dismutase (SOD) levels on the prognosis of patients with ESCC undergoing radiotherapy. METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…All 3 patients with lung cancer requiring tracheal intubation died. The patient mortality rate in our department was lower than the mortality rate The steroid therapy dose and duration are unclear; the usual recommended dose is 40 mg of prednisone daily; [14][15][16][17][18][19][20] no distinction is made between patients with mild RP and patients with severe RP. In the present study, one patient with lung cancer and severe RP who was administered a daily dose of 40 mg methylprednisolone gradually deteriorated; however, his/her condition improved significantly with the daily administration of 80 mg methylprednisolone.…”
Section: Candida Parapsilosismentioning
confidence: 76%
“…All 3 patients with lung cancer requiring tracheal intubation died. The patient mortality rate in our department was lower than the mortality rate The steroid therapy dose and duration are unclear; the usual recommended dose is 40 mg of prednisone daily; [14][15][16][17][18][19][20] no distinction is made between patients with mild RP and patients with severe RP. In the present study, one patient with lung cancer and severe RP who was administered a daily dose of 40 mg methylprednisolone gradually deteriorated; however, his/her condition improved significantly with the daily administration of 80 mg methylprednisolone.…”
Section: Candida Parapsilosismentioning
confidence: 76%
“…We identified a positive correlation between ORC6 expression and the immune infiltration level of CD8 + T-cells in tumors of KIRC and UVM, while a statistical negative correlation between ORC6 expression and the immune infiltration level of cancer-associated fibroblasts, tumor endothelial cells, and Treg cells in certain tumors by means of multiple immune deconvolution methods. Previous studies have demonstrated that immune cell infiltration may contribute to tumorigenesis, development, and metastasis [ 47 49 ]. Cancer-associated fibroblasts are the most abundant cancer stromal cells that induce tumor cell proliferation, therapeutic resistance and immune exclusion [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…These are reports to show that the radio-sensitizing effects are independent of SOD; in such cases, the sensitizing effects are mediated through inhibition of AKT and DNA-PKs (Florczak et al 2009). Elevated levels of circulating SOD improved the quality of life in patients with esophageal cell carcinoma and receiving radiotherapy (Xue et al 2021). Radiation-induced pulmonary fibrosis, a side effect observed in cancer patients receiving radiotherapy, is associated with reduced activities of SOD in lung tissue.…”
Section: Sod Mimicsmentioning
confidence: 97%